Behavioral patterns in latrine use and handwashing in rural western Kenya: Age, time of day, and the role of perceived safety - Noriko Tamari; Heidi E. Brown; Luigi Sedda; Gary L. Christopherson; Katherine D. Ellingson; Stephen Munga; Kacey C. Ernst (PLoS ONE, 2026)
Latrine use enhances health benefits, safety, dignity, and social status. Despite increased latrine coverage, some children and adults do not consistently use latrines. The present study aimed to describe latrine use and handwashing after urination and defecation by age and time of day, and to explore factors associated with latrine use at each time of day. A cross-sectional, population-based survey was conducted from July 17 to September 21, 2023 in western Kenya, targeting individuals aged 4 years or older (n = 528 analyzed). Overall, latrine use tended to be more frequent among adults than children, for defecation than urination, and during the daytime and early morning compared with at night. Handwashing practices after urination and defecation showed similar patterns. For urination, compared with young adults (18–39 years), young children (4–10 years) were less likely to use latrines across all times of day, with reductions of approximately 60–85%. For defecation, compared with adults (18 + years), young children were even less likely to use latrines across all times of day (approximately 90–95% lower likelihood). Similarly, adolescents (11–17 years) had approximately 75% lower latrine use for defecation at night and early in the morning compared with adults. In contrast, individuals who felt safe walking to the latrine at night were substantially more likely to use latrines for both urination and defecation than those who perceived the walk as neither safe nor unsafe or unsafe. Therefore, simple, low-cost interventions, such as promoting the use of flashlights, constructing latrines closer to households, and better connecting sanitation knowledge to daily practices, are crucial for improving sanitation behaviors.